Women's invisible work in disaster contexts: Gender norms in speech on women's work after a forest fire in Sweden - Danielsson, Erna; Eriksson, Kerstin (Disasters, 2022)
The aim of this study is to investigate what women do in disaster situations and how both men and women perceive and discuss the work of women. These patterns were evidenced in the stories that were told following the largest forest fire in the modern history of Sweden in July 2014. The study is based on 31 retrospective interviews with volunteers involved in combating the forest fire and concentrates on stories about the supportive work of women during this disaster. The results indicate that women were praised when they followed traditional norms but were denigrated when they performed what were viewed as male-coded tasks. The stories reveal norms concerning what a woman is and is not by focusing on women's age and clothing and by directly and indirectly questioning their abilities and authority. The norms are also rendered visible by the positive attention that women receive while describing doing what is expected of them
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; catastrophe naturelle; division sexuelle du travail; environnement; europe; normes de genre; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; stéréotypes de genre; suède; thématiques; travail